2021
DOI: 10.3892/mco.2021.2242
|View full text |Cite
|
Sign up to set email alerts
|

Indications for lateral lymph node dissection in patients with rectal neuroendocrine tumors: A case report and review of the literature

Abstract: The optimal surgical indications for small rectal neuroendocrine tumors (NETs) are controversial. Generally, treatment guidelines for rectal NETs >2 cm or with potential lymph node (LN) metastasis recommend formal oncologic low anterior resection (LAR) with total mesorectal excision (TME). However, rectal NETs have the potential to metastasize to the lateral lymph nodes (LLNs). To the best of our knowledge, there are no detailed reports in English on LLN metastasis from rectal NETs. A 47-year-old man diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…From previous reports, 5.8-6.5% of patients with R-NETs were confirmed to have LLNs metastases after rectal resection (24,25). 32 reported cases of LLNs metastases from R-NETs have been reported (3,(24)(25)(26)(27). Among them, Liu, X., et al NET, whose mean tumor size was 2.29 cm, 12 developed LLNs metastases.…”
Section: Discussionmentioning
confidence: 96%
“…From previous reports, 5.8-6.5% of patients with R-NETs were confirmed to have LLNs metastases after rectal resection (24,25). 32 reported cases of LLNs metastases from R-NETs have been reported (3,(24)(25)(26)(27). Among them, Liu, X., et al NET, whose mean tumor size was 2.29 cm, 12 developed LLNs metastases.…”
Section: Discussionmentioning
confidence: 96%
“…However, LPLN metastasis from rectal NETs is very rare, and there are very few reports written in the English language. Fujii et al [ 14 ] summarized 8 and 4 reported cases of synchronous and metachronous LPLN metastasis from rectal NETs, respectively, and only 2 case reports were written in English. A total of 8 patients (66.6%) showed no metastatic lymph nodes in the mesorectum and were identified as skip metastases, and 3 patients showed a primary tumor ≤ 10 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests only a small number of patients have mesorectal metastases; only 3/8 patients undergoing LAR and synchronous TME for rectal NET had lymph node metastases in the mesorectum. 57 As mentioned above, for lesions >2 cm, the likelihood of LN and distant metastasis is higher and full imaging is always required. TAMIS can be performed if patients have comorbidities precluding more major resection.…”
Section: Abdominoperineal Resection (Apr) With Tmementioning
confidence: 99%